Herpes Simplex Virus Epithelial Keratitis In Vivo Morphology in the Human Cornea - Tabery, Helena M. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Herpes Simplex Virus Epithelial Keratitis provides a kind of ‘living histology’, revealing both morphological and dynamic features of the disease, and explaining the mechanisms behind them. It discusses in detail: ° the result of herpes simplex virus impact on the living human epithelium ° the step-by-step dynamics of healing during a successful treatment ° the complications and sequelae of infection The case studies presented demonstrate the application of these observations in clinical practice. This unique guide offers insights helpful in differential diagnostics and the recognition of lesser known variants, as well as complications. It is also useful for the follow–up of treatment results and the differentiation between an active infection and sequelae. It is an invaluable aid for ophthalmologists and researchers working with ocular surfaces.